Institutionalizing Humanitarian Diplomacy as Statecraft: The Jordanian Model of Small-State Foreign Policy during the Gaza Humanitarian Crisis - Gridzanda Magna Yanudza (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Humanitarian diplomacy has emerged as an increasingly important instrument of foreign policy for small states seeking to enhance diplomatic influence while maintaining domestic and regional stability. This study examines Jordan’s humanitarian diplomacy during the Gaza humanitarian crisis from October 2023 to June 2026, focusing on how humanitarian action was institutionalized as a component of foreign policy and statecraft. Employing an empirical qualitative single-case study and qualitative content analysis, the research examines official documents from Jordanian governmental institutions, humanitarian organizations, international institutions, and relevant international legal instruments, supported by academic literature on small-state diplomacy and humanitarian diplomacy. The findings demonstrate that field hospitals, humanitarian airdrops, medical evacuations, aid convoys, and diplomatic advocacy operated as interconnected instruments that combined civilian protection with diplomatic engagement and strategic balancing. Humanitarian diplomacy enabled Jordan to strengthen regional cooperation, maintain diplomatic flexibility among competing actors, respond to domestic political expectations, and enhance international legitimacy despite economic and geopolitical constraints. The study proposes a Jordanian Model of Humanitarian Diplomacy characterized by institutional integration, operational humanitarian engagement, multilateral coordination, and strategic balancing. The research contributes to Law and Political Authority scholarship by demonstrating how humanitarian action can operate as a legally grounded form of statecraft through which a resource-constrained small state generates diplomatic agency and political legitimacy.